SymCrash: Selective Recording for Reproducing Crashes - Cao, Yu; Zhang, Hongyu; Ding, Sun (ASE 2014, 2014)
Software often crashes despite tremendous effort on software quality assurance. Once developers receive a crash report, they need to reproduce the crash in order to understand the problem and locate the fault. However, limited information from crash reports often makes crash reproduction difficult. Many “capture-and-replay” techniques have been proposed to automatically capture program execution data from the failing code, and help developers replay the crash scenarios based on the captured data. However, such techniques often suffer from heavy overhead and introduce privacy concerns. Recently, methods such as BugRedux were proposed to generate test input that leads to crash through symbolic execution. However, such methods have inherent limitations because they rely on conventional symbolic execution techniques. In this paper, we propose a dynamic symbolic execution method called SymCon, which addresses the limitation of conventional symbolic execution by selecting functions that are hard to be resolved by a constraint solver and using their concrete runtime values to replace the symbols. We then propose SymCrash, a selective recording approach that only instruments and monitors the hard-to-solve functions. SymCrash can generate test input for crashes through SymCon. We have applied our approach to successfully reproduce 13 failures of 6 real-world programs. Our results confirm that the proposed approach is suitable for reproducing crashes, in terms of effectiveness, overhead, and privacy. It also outperforms the related methods.